Methotrexate injections for psoriasis. (19th July 2018) - Tsakok, T.; Jabbar‐Lopez, Z.K.; Smith, C.H.
Summary: This article is a review of a study, published in the Lancet, by R.Warren and colleagues, based in the U.K. and western Europe. The authors compared 17.5mg weekly methotrexate, given by subcutaneous injection, with placebo in 120 patients with moderate to severe psoriasis who had not previously received the drug. The first sixteen weeks of the study were a randomised controlled trial, meaning patients were randomly selected to either receive the drug or a placebo; patients continued an open study on methotrexate for up to a year. The dose was increased to 22.5 mg weekly if they did not improve on the lower dose to achieve PASI 50 at week 24. PASI is used to record the redness, thickness and scaling of a patient's psoriasis and to measure how well a treatment works, as a reduction in the PASI score means a reduction in these symptoms; for example PASI 75 means the patient has a 75% or more reduction in their PASI score from the start. The authors took blood tests and skin biopsies from patients on methotrexate and found changes on microscopic examination, including a decrease in CD3 positive lymphocytes and cytokine markers, and this implies that the drug works by its effect on the immune system. Blood tests showed no significant abnormality. At week 16, 41% of patients on methotrexate achieved PASI 75 improvement, compared to 10% of patients on placebo. The reviewers observed that, although methotrexate is widely used as a systemic treatment for psoriasis, there have been no previous randomised placebo controlled trials. This trial is therefore welcome, although only the first phase is placebo controlled. Traditionally, patients are given a small test dose (e.g. 5 or 7.5mg), and the dose is increased gradually over successive weeks. The investigators encountered no adverse events from starting on a higher dose. The reviewers noted that methotrexate by injection was not compared with the oral form of the drug (taken by mouth), which might be equally effective and is substantially cheaper. The unusually high response to placebo may be due in part to alcohol avoidance, which is advised for patients on methotrexate. The changes on skin biopsy are of interest, but it was not possible to correlate them with clinical response to the drug. Abstract : Linked Article:  Tsakok et al. Br J Dermatol 2018;179 :50–53